2012
DOI: 10.1002/cne.23094
|View full text |Cite
|
Sign up to set email alerts
|

Representation of the brain's superior protocerebrum of the flesh fly, Neobellieria bullata, in the central body

Abstract: The central complex of the insect brain is a system of midline neuropils involved in transforming sensory information into behavioral outputs. Genetic studies focusing on nerve cells supplying the central complex from the protocerebrum propose that such neurons play key roles in circuits involved in learning the distinction of visual cues during operant conditioning. To better identify the possible sites of such circuits we used Bodian and anti-synapsin staining to resolve divisions of the superior protocerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 58 publications
(100 reference statements)
3
25
0
Order By: Relevance
“…We found that miR-133 and henna were only detected in the neuronal cell body of the locust protocerebrum (Figures 3A and Figure S3), which is an important region in determining the behavioral responses by output neurons from the mushroom body [26]. Pale was also widely expressed in the protocerebrum, including the mushroom body and the neuronal cell body.…”
Section: Resultsmentioning
confidence: 94%
“…We found that miR-133 and henna were only detected in the neuronal cell body of the locust protocerebrum (Figures 3A and Figure S3), which is an important region in determining the behavioral responses by output neurons from the mushroom body [26]. Pale was also widely expressed in the protocerebrum, including the mushroom body and the neuronal cell body.…”
Section: Resultsmentioning
confidence: 94%
“…The medial portion of the protocerebrum in fruit fly, Drosophila melanogaster has been shown to receive an input from the subregion in the lateral horn, which receives an input from neurons processing the pheromone [49][50][51] . The superior protocerebrum was also shown to provide an input to the CX in the fly [52][53][54][55] . The input from the CX in the fly has been reported to converge on the lateral side of the inferior dorsofrontal protocerebra 55 , which roughly corresponds to the upper division of the LAL in the moth.…”
Section: Discussionmentioning
confidence: 99%
“…route following and landmark navigation, are integrated with path integration. One region of the CX appears to be anatomically suited to serve as integration site for different strategies: The CBU (fan-shaped body) receives input from many different brain areas via a diverse set of input neurons [86,117,118]. These regions include areas that receive projections from the output cells of the mushroom body and thus could carry information controlling navigation strategies that require long-term memory (route following, landmark navigation, retrieval of averaged path integration vectors).…”
Section: Steeringmentioning
confidence: 99%